Introduction - Matos, F.; Roos, G. (Intellectual capital in a global business landscape: Unlocking strategic opportunities and driving growth, 2025)
In an era where value creation increasingly intertwines profit with societal well-being, sustainability has emerged as a central pillar of modern business strategy. This volume explores how intellectual capital (IC) management can act as a catalyst for sustainable transformation in organisations. Building on the ‘IC 5P for the future’ model—aligned with the United Nations’ principles of People, Planet, Prosperity, Peace, and Partnership—this work examines how effective use of intangible assets supports long-term value creation.